Association Between Pre-diagnostic Dietary Supplements Intake and Ovarian Cancer Survival: Findings From a Prospective Cohort Study in Chinese Women - Gu, Jia-Hui; Gong, Ting-Ting; Wu, Qi-Jun; Liu, Fang-Hua; Wen, Zhao-Yan; Gao, Chang; Wei, Yi-Fan; Yang, Zhuo (Frontiers in Nutrition, 2021)
Background: As a result of a limited number of studies and inconsistent findings, there remains uncertainty in whether pre-diagnostic dietary supplements intake affects survival after ovarian cancer (OC) diagnosis. Methods: The association between pre-diagnostic dietary supplements intake and all-cause OC mortality was examined in the OC follow-up study, which included a hospital-based cohort (n = 703) of Chinese women diagnosed with epithelial OC between 2015 and 2020. Pre-diagnostic dietary supplements information was collected using self-administered questionnaires. Deaths were ascertained up to March 31, 2021 via death registry linkage. Cox proportional hazards were used to estimate hazard ratios (HR) and 95 % confidence intervals (CI) for the aforementioned association. Results: A total of 130 women died during the median follow-up of 37.2 months (interquartile: 24.7–50.2 months). We found no evidence that any pre-diagnostic dietary supplements intake compared with never is associated with OC survival (HR=0.74, 95%CI: 0.47-1.16). Furthermore, our study suggested no association for ever intakes of vitamin A (HR=0.52, 95%CI: 0.07-3.76), vitamin C (HR=0.72, 95%CI: 0.31-1.69), vitamin D (HR=1.07, 95%CI: 0.25-4.48), vitamin E (HR=0.54, 95%CI: 0.07-4.16), multivitamin (HR=0.49, 95%CI: 0.15-1.59), calcium (HR=0.92, 95%CI: 0.51-1.65), and fish oil/DHA (HR=0.32, 95%CI: 0.04-2.37) with OC survival. Interestingly, we only found a detrimental effect of vitamin B supplementation intake (HR=3.33, 95%CI: 1.18-9.37) on OC survival. Conclusions: We found no evidence that any pre-diagnostic dietary supplements intake is associated with OC survival. Considering the lower and lower exposure of dietary supplements before OC diagnosis in the present study, further study are warranted to confirm these findings.